Statin effect on arrhythmogenic cardiomyopathy disease progression (SEARCH): Randomized clinical study protocol - Elena Sommariva; Melania Lippi; Flavia Bruttini; Francesco Cannata; Andrea Baggiano; Marco Schiavone; Gaia Salina; Mariano Sabatino; Giulia Vettor; Rita Sicuso; Francesca Pizzamiglio; Valentina Ribatti; et al. (PLoS ONE, 2025)
Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiac disorder that predisposes affected individuals, especially young patients, to malignant arrhythmias, sudden cardiac death, and heart failure. The disease is characterized by myocardial atrophy and fibro-fatty replacement, predominantly affecting the right ventricle. Current pharmacological treatments primarily aim to alleviate symptoms by addressing arrhythmias and heart failure. These approaches are often complemented by invasive interventions such as implantable cardioverter defibrillators (ICDs) and radiofrequency ablations. However, none of these strategies effectively halts disease progression, highlighting the urgent need for novel disease-modifying therapies. We recently demonstrated that elevated plasma levels of oxidized low-density lipoprotein (oxLDL) correlate with more advanced stages of ACM in patients. Moreover, treatment with atorvastatin, which reduces oxLDL levels, prevented disease manifestation in a mouse model of ACM. Based on these findings, we hypothesize that statins may attenuate disease progression in ACM patients not only through their lipid-lowering effects, but also via pleiotropic actions such as antioxidant, anti-inflammatory, and autonomic modulation. To test this hypothesis, we designed SEARCH (Statin Effect on ARrhythmogenic CardiomyopatHy), an investigator-initiated, multicenter, prospective, randomized, double-blind, placebo-controlled clinical trial, aimed at evaluating the efficacy of atorvastatin in preventing ACM progression (NCT06922994). A total of 102 patients meeting ACM diagnostic criteria will be enrolled and randomized in a 1:1 ratio to receive either atorvastatin 80 mg/die or placebo for 18 months. The primary outcome will be the change in right ventricular global longitudinal strain, a sensitive echocardiographic measure of ventricular function, from baseline to 18 months. Secondary outcomes will include changes in arrhythmic burden, electrocardiography parameters, additional structural and functional cardiac indices, and circulating biomarkers. Tertiary and exploratory outcomes include the validation of risk scores for ACM progression and the identification of variables predicting the best responders to atorvastatin. Participants will undergo a comprehensive evaluation at baseline, 9 months, and 18 months, including cardiology visits, echocardiography, electrocardiography, blood testing, ICD or loop recorder interrogation, and cardiac magnetic resonance imaging (at enrollment and at 18 months only). Additional safety assessments and telephone follow-ups will be conducted throughout the study to monitor treatment adherence and potential adverse events. The SEARCH trial is expected to generate the first clinical evidence on the efficacy of atorvastatin in slowing ACM progression, thereby addressing a major unmet therapeutic need. The findings will shape the design of future large-scale studies and may pave the way for a novel, disease-modifying treatment strategy to improve outcomes and quality of life for patients with ACM.